W-Band Noise Characterization with Back-Gate Effects for Advanced 22nm FDSOI mm-Wave MOSFETs - Quang Huy Le; Dang Khoa Huynh; Wang, D.; Zhixing Zhao; Steffen Lehmann; Thomas Kämpfe; Matthias Rudolph (2020 IEEE Radio Frequency Integrated Circuits Symposium (RFIC), 2020)
This paper presents the W-band noise performance of the 22nm FDSOI CMOS technology. In detail, the mm-wave thin-oxide MOSFETs is characterized comprehensively in term of device geometries using the tuner-based noise measurement approach. To aid the noise analysis and extraction, the following study adopts an accurate small-signal equivalent circuit model validated well with bias-dependence up to 110 GHz. The effects of back-gate bias to the overall noise performance are also addressed in this work. The test devices exhibit low noise figure in the full W-band 75-110 GHz. Besides, NF min of 2.8 dB and 3.6 dB is recorded at 94 GHz respectively for the n- and p-FETs with 18nm gate-length (N f = 32, W f = 1.0 µm). The result of this study indicates the comparable performance of the 22nm FDSOI technology to other candidates for W-band applications.